Lived Experience, Historical Consciousness and Narrative: A Combinatory Aesthetics Ethic (Asian Journal of Social Science Studies, 2016)
In this paper I introduce the conception of an “aesthetics ethic” conditioning historical consciousness and writing. The aesthetic ethic is a concept that touches on epistemological, cognitive, aesthetic, experiential, linguistic and ontological qualities that are very much in accord in both historiography and historical novelization. By way of this synthesis, I posit a strong, binding amalgamation that links these two genres. There are a number of transacting ideas and methodological approaches in this work. The focus in this paper is the aesthetic ethic, proper. The aesthetic ethic is a dynamic, densely deliberative field comprising individual and community historical experience, embedded within profoundly aesthetic and conscious contexts, in which history is first lived, and historical writing by historians and historical novelists is then composed. The aesthetics ethic constitutes an environmentality studded with manifold elements of subjectivity, objectivity and intersubjectivity; imagination and artfulness; intentionality and actualization; enunciation and circumscription; reference and contrivance; experience and conjecture; intellection and apperception; contingency and modality. The aesthetics ethic will, I hope, prove to be a useful map revealing details about how historians and historical novelists perceive (one of the source meanings of aesthetic) common facets of historical consciousness amidst a true kinship (one of the source meanings of ethic) of overlapping interests, methods and aims. By way of this overall amalgamation, the synthesis I have referred to is effected, linking the writings and interpretations of historians and historical novelists in important ways. I refer to a number of important analysts in this study, perhaps most importantly John Dewey, Hayden White and Frank Ankersmit. As well, an important phase of analysis is my study of Daniel Wickberg’s theory of “histories of sensibilities”.